PENGARUH PROGRAM PEMUTIHAN PAJAK DAERAH TERHADAP PENERIMAAN PKB DAN BBNKB TAHUN 2024 DI UPT PPD PONOROGO - Wilindra, Felina; Nona Jane Onoyi (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This study aims to determine the effect of the East Java tax amnesty program in 2024 on PKB and BBNKB revenues at the UPT PPD Ponorogo. The effect of this amnesty program can be seen from the number of taxpayers who utilize it and how much the increase in PKB and BBNKB revenues is before and after the tax amnesty. The data used in this study are secondary data. The object of this study is the UPT PPD Ponorogo with the dependent variable being PKB and BBNKB revenues and the independent variable being the tax amnesty program. The research method used is descriptive quantitative and comparative. This method provides an overview and description of the numerical data that has been collected which will then also be used to compare data before and after the amnesty program. The results of the study show that the 2024 tax amnesty program has a positive effect on PKB revenues but has a negative effect on BBNKB because the tax amnesty resulted in the UPT PPD Ponorogo losing 8.87% of the potential from the BBNKB sector. The regional tax amnesty program is effective in increasing revenues in the PKB sector but is not effective for revenues from the BBNKB sector. However, this tax amnesty program is very beneficial for taxpayers and in the long term can increase PKB revenues so it is hoped that it can be held again in the following years.